Enhancing Literacy and Uncovering Hidden Talents in Sri Lankan Prisoners: A Project in Welikada prison - Sajeewani, H.W.K. (Library, University of Jaffna, 2024)
People are imprisoned for committing a criminal offense and punished after being convicted in front of the law. It is one of the responsibilities of the prison administration to rehabilitate and socialize the imprisoned people after transforming them into decent. Education, rehabilitation, and effective use of time can be used as a method for socialization. The optimum rehabilitation process can be done by developing literacy skills, spiritual harmony, and artistic skills of prison inmates. This can contribute to their reintegration into society and overall public safety. The objectives of the project were to improve literacy skills among inmates; to identify and develop their hidden personal skills that can lead to suitable employment opportunities after release; to develop the self-confidence of the inmates; to strengthen community and family relationships with the inmates by having positive attitudes towards them in the entire society.
Keywords: Hidden talents; Prisons; Literacyskills; Information Literacy; SriLanka